(3eSFhdjI GdTQjc aj TQcI GdTNU GdhGMO aj VhA GdbGfhf (B(4) (3dSfI (B2018 :s (3OQGSI ebGQfI (B/s - (3eQhI SjO eMeOs; (3Ndjd ajcJhQ JGOQSs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2022)
(3JfU GdeGOI (B(4) (3ecQQ ef GdbGfhf (B159 (3dSfI (B1981(3e GdeYOd HGdbGfhf Qbe (B(4) (3dSfI (B2018 (3Ydi Cfg (S0(3TQcI GdTNU GdhGMO gj TQcI jeJdc QCSeGdgG HGdcGed TNU hGMO, ShGA cGf WHjYkjG Ch GYJHGQkjG, hPdc HeG dG jJYGQV eY CZQGVgG hdG jSCd eDSS GdTQcI Yf GdJRGeGJgG EdG aj MOhO QCS GdeGd GdeNUU dgG(B. (3Ef eSFhdjI eDSS TQcI GdTNU GdhGMO eMOhOI HebOGQ QCS GdeGd GdPj bOeg YfO JCSjS GdTQcI , hdG jLhR eWGdHJg GdTNUjI Yf Ojhf GdTQcI, hPdc dCf ddTQcI PeI eGdjI eSJbdI Yf PeJg GdeGdjI(B. (3hdcf gfGc MGdGJ jchf ajgG eDSS TQcI GdTNU GdhGMO eSFhdjI ZjQ eMOhOI cGdBJj(B: - (3EPG bGe HShA fjI HJUajI GdTQcI Ch hba fTGWgG bHd GfJgGA eOJg Ch JMbjb GdZQV ef EfTGAgG(B.(3EPG NdW Hjf PeJg GdeGdjI hGdPeI GdeGdjI ddTQcIEPG CHQe YbhkOG Ch JUQaGJ HGSe GdTQcI JMJ GdJCSjS, hde Jcf gPg GdYbhO Ch GdJUQaGJ dGReI dJCSjS GdTQcI(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, (B2022(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3U(B. 250-268.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3QCS GdeGds; (3TQcI GdTNU GdhGMOs; (3NUGFU TQcg GdTNU GdhGMOs; (3GdTQhW GddGReg dJGSjS TQcg GdTNU GdhGMOs; (3eSFhdjg ZjQ eMOhOgs; (3eSFhdjg eMOhOgs; (3eSFhdjg GdeDSSs; (3Peg eGdjgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs